Argumentative forms around the legitimation of anti-sciences in the mozambican academy - Abdul, Linda Jivane (Seven Editora, 2023)
In this communication, we seek to identify the argumentative forms that can be sustained around the debate on the legitimation of anti-sciences in the Mozambican academy. The anti-sciences were seen as pseudo-knowledge, because they were not guided by the same epistemological principles defended by modern science. It all begins with the model of rationality developed by modern epistemology with the advent of the scientific revolution (century. XVI-XVIII) which had as the basis of foundation of its discourse, the exactness of the natural sciences; jeopardizing the possibility of a possible communication between different types of knowledge. There is an urgent need for the practicality of the discourse already begun on the rescue and legitimation of anti-sciences in the Mozambican academy. In general, this communication intends to reflect on the applicability of the philosophical discourse that points out the ineffectiveness of the exclusion of anti-sciences in the academy led by modern science. Specifically, it intends to present the already existing argumentative forms that validate the importance of rescuing the anti-sciences. From the methodological point of view, this communication is guided by the bibliographic consultation, which consists of the collection and reading of the previously collected material and hermeneutics as a technique that allows the interpretation of texts that deal with the theme. We also help ourselves with critical reflection, through argumentation in order to clarify our debate. The research is guided by the following starting question: how do exclusionary discourses serve to devalue local knowledge? In this way we will show the limits of modern science and therefore the emergence of the need to open space for a communication between the destintos saberes in the Mozambican academy. DOI:https://doi.org/10.56238/uniknowindevolp-135